Estimates of the prevalence of autism spectrum disorder in the Middle East and North Africa region: A systematic review and Meta-Analysis - Aishat F. Akomolafe; Bushra M. Abdallah; Fathima R. Mahmood; Amgad M. Elshoeibi; Aisha Abdulla Al-Khulaifi; Elhassan Mahmoud; Yara Dweidri; Nour Darwish; Duaa Yousif; Hafsa Khalid; Majed Al-Theyab; Muhammad Waqar Azeem; et al. (BMC Public Health)
Abstract Background Prevalence estimates for autism spectrum disorder (ASD) in the Middle East and North Africa (MENA) region are not readily available, amid a lack of recent evidence. In this study, we estimated the prevalence of ASD in the MENA region by synthesising evidence from published studies. Methods We conducted a systematic review and meta-analysis, searching PubMed, EMBASE, Scopus, and CINAHL for studies assessing ASD prevalence in the MENA region. Risk of bias was assessed using the Newcastle Ottawa scale. A bias-adjusted inverse variance heterogeneity meta-analysis model was used to synthesize prevalence estimates from included studies. Cochran’s Q statistic and the I2 statistic were used to assess heterogeneity, and publication bias assessed using funnel and Doi plots. Results Of 3,739 studies identified, 19 met the inclusion criteria, published during the period 2007–2025, from Iran, Oman, Libya, Egypt, Saudi Arabia, Lebanon, United Arab Emirates, Bahrain, and Qatar, Iraq. Country specific prevalence estimates ranged from 0.01% in Oman in 2009 to 6.50% in one study from Iraq in 2024. The overall prevalence of ASD in the MENA region was 0.14% (95%CI 0.02– 0.36%), with significant heterogeneity (I2 = 99.8%). Overall ASD prevalence was 0.04% (95%CI 0.00–0.13, I2 = 99.4%) for studies done before 2015 and 0.45% (95%CI 0.17–0.87, I2 = 99.4%) for studies after 2015. Overall ASD prevalence was high in studies that used the Modified Checklist for Autism in Toddlers (M-CHAT) only [1.66% (95%CI 0.15–4.33, I2 = 97.5%)] while the overall ASD prevalence was 0.14% (95%CI 0.00-0.46, I2 = 99.9%) for studies that used the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria for diagnosis. Conclusion Estimates of the prevalence of ASD vary widely across the MENA region, with variability in ASD prevalence estimates by diagnostic methods and sampling approaches. While the data suggest a possible increase in prevalence during the study period, this observation warrants further investigation through more robust, longitudinal, and methodologically consistent studies. Registration PROSPERO registration ID CRD42024499837.